Perbedaan Tingkat Kebahagiaan K-Popers dan Non K-Popers di SMK Negeri 1 Martapura - Leni Maulida; Rudi Haryadi (INDONESIAN COUNSELING AND PSYCHOLOGY, 2023)
Happiness is a positive feeling that is felt by every individual, where this happiness has a relationship between pleasure, satisfaction, and happiness in life. The topic of happiness is interesting to discuss, especially if this topic of happiness compares between two groups in order to find out which group has the higher level of happiness.  This study aims to determine the differences between the two groups, namely groups of k-pop fans and non-k-pop fans. The sample in this study were 18 k-pop fans and 18 non-k-pop fans from SMK Negeri 1 Martapura. The measuring instrument used for this research is the Happiness Scale. Assumption test in this research is in the form of normality test and homogeneity test. In the Assumption Test results, the results obtained that the two groups, namely fans and non-fans of k-pop, show that the data is normally distributed.  Researchers analyzed the data using Two Independent Sample T-Test through an application, namely SPSS for windows version 25 with a result of 0.327 with a probability value of p > 0.05. From the results of the data analysis, it can be seen that there is no significant difference between the level of happiness of k-pop fans and non-k-pop fans.